Colony site characteristics of sympatric breeding tern species on the Mond Islands, the Persian Gulf - Tayefeh, Farhad Hoseini; Hussin, Mohamed Zakaria; Amini, Hamid; Ghayoumi, Razieh; Khaleghizadeh, Abolghasem (Taylor & Francis, 2017)
We have investigated characteristics of colony site of three sympatric breeding tern species on small islands of a subtropical region, the Persian Gulf. The three most populous ground-nesting waterbird species – Bridled Tern Onychoprion anaethetus, Lesser Thalasseus bengalensis and Greater Thalasseus bergii Crested Terns – were studied during the 2009–2011 breeding seasons. The average area size of mixed colonies was 454 m2. The density of nests of the Bridled Tern was 846 nests/ha. The proportion of the number of nests in a mixed colony for Lesser Crested Tern (5546 nests) was approximately 10-fold compared to the Greater Crested Tern (542 nests). The density of Bridled Tern nests/ha was significantly higher in areas with 50–75% vegetation cover (>1200 nests/ha) than in areas of <5% vegetation cover (72–105 nests/ha) (p < 0.05). Mixed colonies of the Lesser and Greater Crested Terns were located on unvegetated land, at an average distance of 4.1 m to vegetation, and on sandy soil (79.4% on average) and above high spring tide water lines (0.59 m on average). There were more potential nesting areas than occupied areas for the mixed colonies of the Lesser and Greater Crested Terns, indicated that they did not face nest site limitation.